KONTRIBUSI SUPERVISI KEPALA SEKOLAH DAN KOMITMEN GURUTERHADAP KINERJA GURU SDN DI KECAMATAN BANGKOKABUPATEN ROKAN HILIR - Kartini1; Isjoni; Azhar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to determine the effect of principals' supervision and teachers' commitment either partially or jointly on the elementary school teachers' performance in Kecamatan Bangko, Kabupaten Rokan Hilir. The phenomenon in this district was that the teachers did not have the optimal ability to develop a syllabus and lesson plan (RPP), which led to an unattractive learning atmosphere. Besides, teachers' ability in classroom management was still lacking, so it was challenging for teachers to create a conducive atmosphere and a fun learning process in the classroom. The teacher could not maximally utilize the media; as a result, distributing messages (subject material) to students was not optimal. In addition, the teacher did not vary the learning methods, resulting in the students' boredom in the teaching and learning activities. This study was descriptive quantitative research. The data were collected through a questionnaire given to 112 teachers randomly selected as samples using the census sampling method. In this study, the respondents responded to the questionnaire in the form of a Likert scale. Then, the data were analyzed by multiple linear regression and data processing using the Statistical Package for Social Science (SPSS) program. The study results revealed that the principals' supervision partially influenced teachers' performance. It implied that the principals' supervision became a vital variable to consider to improve teachers' performance. Likewise, the teachers' commitment partially affected their performance. The higher the teachers' commitment, the better the teachers' performance was. Overall, both the principals’ supervision and career development affected the performance of Elementary School teachers in Kecamatan Bangko, Kabupaten Rokan Hili